Hawtrey's the Gold Standard in Theory and Practice - Marget, Arthur W. (Quarterly Journal of Economics, 1927)
Journal Article Hawtrey's the Gold Standard in Theory and Practice Get access Arthur W. Marget Arthur W. Marget University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 1, November 1927, Pages 140–152, https://doi.org/10.2307/1885369 Published: 01 November 1927